Screening of 50,539 newborns for congenital hypothyroidism: optimization of TSH cut-off values and seasonal impact in clinical practice - Zhang, Lixian; Lin, Kun; Han, Xinrong (Frontiers in Endocrinology, 2025)
ObjectiveTo analyze the incidence of congenital hypothyroidism (CH) in Putian, optimize the thyroid-stimulating hormone (TSH) screening cut-off value, and improve diagnostic efficiency and accuracy.MethodsA retrospective analysis was conducted on TSH screening data from 50,539 newborns in Putian between July 2020 and November 2022. TSH concentrations in dried blood spots were measured using time-resolved fluorescence immunoassay (TRFIA). The optimal cut-off value was evaluated using percentile analysis and receiver operating characteristic (ROC) curves. Confirmatory tests included serum TSH, free thyroxine (FT4), and thyroid ultrasound.ResultsThe detection rate of CH was 1:1,232 (41 cases), with an overall detection rate of 1:555 (including 50 cases of hyperthyrotropinemia). The P99 percentile method determined a TSH cut-off of 11.1 μIU/mL, while ROC curve analysis indicated an optimal cut-off range of 9.33–9.43 μIU/mL (sensitivity 100%, specificity 98.1%, area under the curve [AUC] = 0.997, P < 0.0001). Adopting a revised cut-off of 9.5 μIU/mL reduced recall rates by 10.62% but missed 1 case of hyperthyrotropinemia. Initial TSH positivity exhibited seasonal fluctuations, with higher rates in winter than summer. Among 68 initially negative cases with subsequent elevated venous TSH, 2 were confirmed as CH, highlighting the need for secondary screening in high-risk groups.ConclusionA TSH cut-off of 9.5 μIU/mL optimizes CH screening in Putian, balancing sensitivity (100%) and specificity (98.1%). Seasonal TSH variations and high-risk cases (e.g., preterm infants) highlight the need for tailored protocols. This approach improves screening efficiency and reduces recalls, supporting region-specific adjustments.